Recreational and Preservation Value of Charaideo Maidams of Assam, India - DE, Utpal Kumar; BORAH, Bidyajyoti (Journal of Environmental Management and Tourism; Vol 16 No 1 (2025): JEMT Volume XVI, Issue 1(77), Spring 2025DO - 10.14505/jemt.v16.1(77).03, 2025)
Historical monuments serve as profound connections to the past, embodying cultural, architectural, and societal significance. Historical tourism has played a very important role in generating income and employment in North-East India, especially Assam, as the region is blessed with distinct natural and archaeological resources that attract a huge number of domestic as well as foreign tourists every year. These sites possess both use and non-use economic values, similar to environmental resources, and are valued not only for their direct recreational and educational benefits but also for their option, bequest, and vicarious values. The challenge in determining their true value stems from their non-market nature, where conventional economic mechanisms fall short. This study examines how socio-economic and demographic factors influence visitation to historical sites, using regression analysis, and the recreational benefits enjoyed by visitors at a historical heritage site are estimated employing both revealed and stated willingness to pay (WTP), specifically through the Travel Cost Method (TCM) and the Contingent Valuation Method (CVM). The analysis shows that the distance travelled and the costs they incur have a significantly negative impact on how often they visit a site, while higher income and education levels positively influence visit frequency. The estimated recreational benefits, based on both revealed and stated WTP for the site's preservation and enhancement, suggest that increasing recreation charges through policy changes could be justified.